First record of Chiococca motleyana (Rubiaceae) in the tropical deciduous forests of the Central Depression of Chiapas, Mexico - Vicente Rivera, Luis Humberto; Cruz, Angelita López; Vicente Rivera, Blanca Nidia; Pérez Farrera, Miguel Ángel (Instituto de Ecología, A.C., 2018)
Background and Aims: In the last decades, floristic studies of tropical deciduous forests have increased; they indicate that this vegetation type supports high levels of diversity and endemism, at the same time being one of the most threatened ones by change in land use. The objective of this work is to present a new record of a species of Chiococca in Chiapas.Methods: During botanical explorations in the Central Depression of Chiapas, specimens belonging to the Chiococceae tribe of family Rubiaceae were collected. The specimens were identified as Chiococca motleyana (based on Asemnantha pubescens), using specialized literature and confirmation by family specialists. Specimens of local and regional herbaria were examined; the online databases of foreign herbaria were also consulted. The specimens were deposited in the Herbarium Eizi Matuda (HEM).Key results: Having found Chiococca motleyana in Chiapas shows the floristic affinities that exist between Chiapas, Guatemala, Belize, and the states that make up the Yucatan Peninsula. Chiococca motleyana inhabits patches of secondary vegetation of tropical deciduous forest immersed in a matrix of agricultural landscape.Conclusions: The patches of the secondary dry forest play a key role as refuges for endemic species and native flora of the region. It is necessary to increase the efforts of botanical exploration to complete the knowledge of these ecosystems at risk.